A case report of prolonged COVID‐19‐positive RT‐PCR for five months - Zeinab Siami; Saeidreza Jamalimoghadamsiahkali; Armin Khavandegar (Clinical Case Reports, 2022)
Abstract The COVID‐19 gold standard assessment tool remained the RT‐PCR of upper respiratory tract specimen extracted by the nasopharyngeal swab. A positive result would decrease through a three‐week course and eventually be undetectable. The maximum duration of viral shedding is 83 days. Besides, COVID‐19 RT‐PCR remained positive for 74 days in a patient suffering from lymphoma. In this study, we have presented a 56‐year‐old male patient, a known case of lymphoma since 2015, who experienced many episodes of chemotherapy with a five‐month positive RT‐PCR COVID‐19 laboratory test and finally was intubated and then died of opportunistic pulmonary infections. COVID‐19 patients with concurrent lymphoma failed to remove the virus thoroughly, despite providing appropriate treatment regimens.